Different Resolution Merging Methods For Environmental Areas Extraction (Journal of Engineering, 2012)
The usage of remote sensing techniques in managing and monitoring the environmental areas is increasing due to the improvement of the sensors used in the observation satellites around the earth. Resolution merge process is used to combine high resolution one band image with another one that have low resolution multi bands image to produce one image that is high in both spatial and spectral resolution. In this work different merging methods were tested to evaluate their enhancement capabilities to extract different environmental areas; Principle component analysis (PCA), Brovey, modified (Intensity, Hue ,Saturation) method and High Pass Filter methods were tested and subjected to visual and statistical comparison for evaluation. Both visual and statistical comparison showed that High Pass Filter method have highest visual enhancement and highly maintained the quantitative information of the original image, Modified (Intensity, Hue, Saturation) method showed good visual and statistical results in comparison with PCA and Brovey method which had the lower results respectively.